Exploring Feminism Through the Symbolic Meaning of Perempuan Yang Memeram Sunyi Pada Jantung Angin By Ali Zulfikar - Myesha, Romlah Arome Elladine; Puspitasari, Desi (Universitas Pahlawan Tuanku Tambusai, 2025)
This research has explored feminism through the symbolic meaning in the poem Perempuan Yang Memeram Sunyi Pada Jantung Angin by Ali Zulfikar. The aim of the study is to analyze the symbols in the poem using Charles Sanders Peirce's semiotic approach and to understand the representation of women's experiences in the context of feminism. The research employs a descriptive qualitative method with data collection techniques of reading and note-taking. Data analysis follows the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of the study show that symbols such as pohon, hujan mawar, and rantai yang dipatahkan represent strength, resilience, and resistance to patriarchal oppression. This poem not only serves as an aesthetic work but also as an effective medium to voice issues of gender injustice. Zulfikar's work significantly contributes to the feminist discourse in Indonesian literature, providing new insights into the representation of women in a socio-cultural context.